1998
DOI: 10.1103/physreve.57.6875
|View full text |Cite
|
Sign up to set email alerts
|

Branching and percolation in lecithin wormlike micelles studied by dielectric spectroscopy

Abstract: Lecithin water-in-oil microemulsions have been shown to form long polymerlike micelles. Dielectric spectra of this system are characterized by two dispersions. The high frequency dispersion, related to the head-group rotation of the lecithin molecule, displays a different dependence on water addition in the same two regimes that show up differently in the dynamics measured with several other techniques. The low frequency dispersion is due to a polymeric Rouse/Zimm type mode, which above a certain concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 40 publications
4
33
1
Order By: Relevance
“…The presence of branches in lecithin reverse micelles in isooctane was rst suggested on the basis of a dielectric spectroscopy study where an increase in conductivity at high water content was interpreted as the indication of the formation of a connected network. 40 Reassuringly, the same experiments did not nd evidence of branches in cyclohexane. 33 The conclusive proof of branch formation was achieved by using the same PGSE-NMR approach that ruled out the branches in cyclohexane.…”
Section: Connected Wormlike Reverse Micelles: Living Networkmentioning
confidence: 81%
“…The presence of branches in lecithin reverse micelles in isooctane was rst suggested on the basis of a dielectric spectroscopy study where an increase in conductivity at high water content was interpreted as the indication of the formation of a connected network. 40 Reassuringly, the same experiments did not nd evidence of branches in cyclohexane. 33 The conclusive proof of branch formation was achieved by using the same PGSE-NMR approach that ruled out the branches in cyclohexane.…”
Section: Connected Wormlike Reverse Micelles: Living Networkmentioning
confidence: 81%
“…Conductivity measurements provide a means of determining whether a microemulsion is oil-continuous or water-continuous, as well as providing a means of monitoring percolation or phase inversion phenomena [62][63][64]. Dielectric measurements provide the structure and dynamic feature of microemulsion systems [65][66][67]. But all the macroscopic properties depend on the microscopic structure.…”
Section: Microemulsion Characterisationmentioning
confidence: 99%
“…To formulate a model for ε micelles * , we built on the approach of Cirkel et al In their original work, they described the dielectric response of dilute WLMs as being composed of two relaxation modes, one associated with chain motion, ε chains * , and the other due to rotational motion of surfactant headgroups, ε headgroups * , within the micelle core. , They confirmed that the correct functional form for the latter is the Debye equation as the mode distribution associated with rotation of the headgroup is narrow. We adopted this same convention.…”
Section: Resultsmentioning
confidence: 89%
“…Cirkel et al observed that the low-frequency dielectric response was the same as the rotational diffusion time of a micelle determined from light scattering . Further, these micelles exhibit the Kerr effect, , and the observed rotational relaxation times were shown to correlate well with those in dilute solutions and with the combination of reptation and breakage processes when unbranched chains were entangled. These results showed that, when measurements are made on unbranched chains, the dielectric response could be described using a similar framework describing the dielectric properties of the polymers.…”
Section: Introductionmentioning
confidence: 92%